Emotional Exhaustion and Job Demands-Resources as Correlates of Library Personnel’s Work Performance in Higher Education Institutions - Flores, Llana Rose Francesca; Dequito, Estela (Journal of Interdisciplinary Perspectives, 2025)
This study examines the relationship between emotional exhaustion, job resources, and work performance among library personnel in higher education institutions. Addressing the research gap on how these factors interact, the study aims to determine whether emotional exhaustion and job resources significantly influence work performance. Employing a descriptive-correlational research design, data were collected through census sampling, covering 207 library personnel across the Caraga Region. Validated survey instruments measured emotional exhaustion, job demands, job resources, and work performance. Statistical analyses, including Mean and Pearson's correlation, assessed relationships among the variables. Findings revealed that emotional exhaustion was moderately present but did not significantly impact work performance. Job demands and resources were moderately manifested, while work performance remained consistently high across task, contextual, and adaptive domains. Although job demands and resources significantly contributed to emotional exhaustion, they did not directly influence work performance. Therefore, it is recommended that higher education institutions focus on enhancing job resources and implementing strategies to manage emotional exhaustion and support library personnel effectively.